Analysis of the antibacterial and thrombolytic activity of citrus sinensis peel extracts - Subi, Shagufta Jasmin (BRAC University, 2017)
This project report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Pharmacy, 2016